Pengaruh Edukasi Pencegahan Bullying terhadap Sikap dan Perilaku Bullying pada Siswa Kelas VII di SMPN 1 Padang Laweh, Kabupaten Dharmasraya Tahun 2024 - Ningsih, Ika Margi; Erfiana, Erma; Enopadria, Costarin (Fakultas Ilmu Kesehatan Universitas Dharmas Indonesia, 2024)
According to Programmer for International Student Assessment (PISA) in 2023, Indonesia is ranked 5th in terms of bullying cases in the world out of 78 countries surveyed, where 42% of 15-year-old students in Indonesia become victims of bullying within 1 month. Based on the Indonesian Child Protection Commission (KPAI) 2023, it is stated that 236 cases of physical and psychological violence occurred. This research aims to determine the effect of bullying prevention education on students' attitudes and behavior. This research uses a Pre-Experimental research type using a design (One group pre-post test), research time 06 June 2024 at SMPN 1 Padang Laweh with a population of 60 students with a total sampling technique. Based on univariate analysis, it was found that the majority, namely 39 respondents (65%), had a positive attitude, and almost half, namely 28 respondents (46.7%) had low bullying behavior before being given bullying prevention education. Based on the Wilcoxon test, the results of the research on the influence of bullying prevention education on students' attitudes showed a P-value = 0.683>0.05. It could be concluded that bullying prevention education had no effect on students' bullying attitudes. Based on the results of the Paired Sample T-Test, it was found that the P-Value = 0.000 < 0.05, it can be concluded that there is an influence of bullying prevention education on student behavior. It is hoped that students will be able to understand and always apply attitudes and behavior to prevent bullying at school and in everyday life.